ANALISIS TEKNIK PENILAIAN GURU TERHADAP NILAI RAPORT SISWA DI MASA PANDEMI COVID-19 - Rifaatul Mahmudah; Muh. Yazid (Program Studi PGSD Universitas Flores, 2022)
During the pandemic Covid- 19, parent of many student who helped their children do the tests at home. As a result, the pros and cons of other students’ parents emerge against the teacher’s assessment tecniques. This problem must be analyzed and revealed based on the correct assessment technique. In order to get a valid report card value. Analisys this reseach was supported by a case study method involving 30 respondents. 13 teacher responses, 15 students parents and 2 experts in the field of learning evaluation. Instrument in the form of an interview questionnaire. The result of the analisys responses of this research interview are; 1) Teachers, of the 13 respondents 64% gave the value of srudent report cards using the data of previous learning outcomes (in odd semester). And 36% used repeat scores from home. 2) Student ‘parents’ responses to the value of their children’s report cards during the co-pasndemic period -19. Of the 15 respondent 25% saw the assessment tecniques conducted by the teacher based on previous learning outcomes data (in odd semester). And 55% used repeat scores from home. 20% saw both and 3) Expert response, the assessment technique of student report cards in the pandemic Covid-19. Both experts are of the same opinion that it must be based on the CAP assessment (Cognitive, Affective, Psychomotor) equipped with instruments and LKPD.